Anyone ??
I’m confused

Anyone ??Im Confused

Answers

Answer 1
+2+(-3)+(-1)+4(-5)+(-3) ok so first 2 is positive and 3 is negative there both different signs so u subtract +2+(-3)=-1+(-1)=0+4=4+(-5)=-1+(-3)=-4 your answer is 4

Related Questions

how to determine if its a proportional

Answers

You have to see if they are all moving up at a constant rate. You can check this by subtracting $17.40 from $21.75. It is $4.35. Then multiply $4.35 by 46. If it is not equal to $200.10, then it is not a proportional relationship. When you multiply it, you actually do get $200.1, which is equal to $200.10. So this is a proportional relationship.

Which proportion correctly shows the equivalence of two ratios?

A. 2:3=27:18
B. 14:35=7:2
C. 4:5=32:40
D. 13:39=6:2

Answers

C. 4:5=32:40 is your answer

Treat each ratio like fractions. Note the equal sign. This means that, when each fraction is simplified, they would be the same.

4/5 = 4/5

(32/40)/(8/8) = 4/5

4/5 = 4/5

(C) is your answer

~Rise Above the Ordinary, Senpai


two angles are supplementary if the sum of their measures is 180°. If one of two supplementary angles measures 85°, what is the measure of the other angle?

Answers

95° because 85 + x = 180 so you do 180 - 85 and get 95

95° because 85 + x = 180 so you do 180 - 85 and get 95

For every 50 emails that Nick sent in a month, he received 30 emails. What is the ratio in simplest form of the number of emails sent to the number of emails received by Nick that month?

Answers

50:30 or 50/30
Every 50 you get 30
Final answer:

The ratio of emails sent to emails received by Nick that month is 5:3 in its simplest form, determined by calculating their greatest common divisor.

Explanation:

The subject of your question is ratios and it falls under the category of Mathematics.

'For every 50 emails that Nick sent in a month, he received 30 emails.' This tells us about a ratio. A ratio is a way to compare amounts of something.

The ratio in this case is the number of emails sent by Nick to the number of emails he received. We express this ratio as '50:30'.

To simplify the ratio, we find the greatest common divisor (GCD) of 50 and 30, which is 10. So, we divide both numbers by 10. Thus, our simplified ratio is 5:3.

This means Nick sent 5 emails for every 3 emails he received, in simplest terms.

Learn more about Ratios here:

https://brainly.com/question/32531170

#SPJ3

Solve the equation 4c^2+7c-5=0 using the quadratic formula.

Answers

[tex]c = \frac{-7+\sqrt{129} }{8}  ,\frac{-77-\sqrt{129} }{8}[/tex]

NEED HELP IMMEDIATELY Which expression is equivalent to one over four n − 16? a. one over four(n − 4)
b. one over four(n − 64)
c. 4(n − 4)
d. 4(n − 64)

Answers

A because just multiply 1/4 by 16 and u get 4

Which phrase correctly orders –23, 11, –17, and 5?


A.
–17 < –23 < 5 < 11

B.
–23 < –17 < 5 < 11

C.
5 < 11 < –17 < –23


D.
–23 < 11 < –17 < 5

Answers

B is in the correct order
B is the correct answer since -23 is the lower at then -17 and so on

Solve the equation using addition or subtraction.
4=q+13
A q=4
B q=17
C q=-9
D q=-2

Solve the equation using addition or subtraction.
5.5= -2+d
A d=5
B d=7.5
C d=5.5
D d=3.5

Solve the equation using multiplication or division
-7y=28
A y= -4
B y=4
C y=14
D y=35

Solve the equation using multiplication or division
-13 = m/ -5
A m=13/5
B m=45
C m=65
D m= 5/13

Answers

Answer:

1. Solve the equation using addition or subtraction.

[tex]4=q+13[/tex]

Taking like terms on one side, we get

[tex]4-13=q[/tex]

=> [tex]-9=q[/tex]

or [tex]q=-9[/tex]    (option C)

2. Solve the equation using addition or subtraction.  

[tex]5.5= -2+d[/tex]

Taking like terms on one side, we get

[tex]5.5+2=d[/tex]

So, [tex]d=7.5[/tex]    (option B)

3. Solve the equation using multiplication or division

[tex]-7y=28[/tex]

Dividing both sides by 7, we get

[tex]-y=4[/tex]

or [tex]y=-4[/tex]    (option A)

4. Solve the equation using multiplication or division

[tex]-13=\frac{m}{-5}[/tex]

Cross multiplying -13 and -5 to get the value of m

[tex]m=(-13)(-5)[/tex]

[tex]m= 65[/tex]      (option C)

The solutions of the equations are =

1) C) q = -9.

2) B) d = 7.5.

3) A) y = -4.

4) C) m = 65.

Given are the equation we need to solve them,

Let's solve the equations one by one:

1) 4 = q + 13

To isolate q, we can subtract 13 from both sides of the equation:

4 - 13 = q + 13 - 13

-9 = q

Therefore, q = -9.

The correct answer is C) q = -9.

2)5.5 = -2 + d

To isolate d, we can subtract -2 from both sides of the equation:

5.5 - (-2) = -2 + d - (-2)

5.5 + 2 = d

7.5 = d

Therefore, d = 7.5.

The correct answer is B) d = 7.5.

3) -7y = 28

To solve for y, we can divide both sides of the equation by -7:

(-7y) / (-7) = 28 / (-7)

y = -4

Therefore, y = -4.

The correct answer is A) y = -4.

4) -13 = m / -5

To isolate m, we can multiply both sides of the equation by -5:

-5 x (-13) = m

65 = m

Therefore, m = 65.

The correct answer is C) m = 65.

Learn more about Equations click;

https://brainly.com/question/29538993

#SPJ6

A batch of cookies for 3/4 cup of flour.You want to make 1/2 of a batch.How much flour do you need?

Answers

For the total batch you need 3/4 cup and you only want one half of that, so you need to multiply 3/4 by 1/2

[tex] \frac{3}{4} \times \frac{1}{2} = \frac{3}{8} [/tex]

First will make the fraction is easier by turning it into 6/8 but because we’re halving it the we only halve the numerator, so it’s 3/8.

If this can’t be understood I’d gladly help elaborate

Round the sum of 43.524 +3.004 to the nearest tenth

Answers

Answer:

46.50

I hope this helped


43.524 +3.004= 46.528

rounded you should get 46.530

sorry if i couldnt help hope i did! :)


Two jets leave an air base at the same time and travel in opposite directions. One jet travels 60 /mih faster than the other. If the two jets are 7848mi apart after 6 hours, what is the rate of each jet?

Answers

slower jet speed is x

[tex]6 x + 6(x + 60) = 7848 \\ 12x + 360 = 7848 \\ x = 624[/tex]
so the two speeds are 624 and 684

The speed of the slower jets and faster jets are 624 mi / Hr and 684 mi/hr respectively.

What is speed?

Speed is defined as the ratio of the time distance travelled by the body to the time taken by the body to cover the distance.

Let the speed of a slower jet be represented as 'x'

Now Given:

one jet travels 60 mph slower than the other.

Hence Speed of a faster jet will be = x  +   60

Distance = 7848  miles

Time = 6 hrs

Now we know that;

Distance is equal to the product of speed and time.

Framing in the equation we get;

Distance = (Speed of Faster Jet + Speed of Slower jet) × Time.

Substituting the given values we get;

7848  =  ( x  +  x  +  60  )  6

7848  =  12x  +  360

x  =  624

Speed of slower jet = 624 miles/hr

Speed of faster jet = 624  +  60  =  684 miles/hr

Hence Speed of the Faster jet is 684 miles/hr and the speed of the slower jet is 624 miles/hr.

To know more about Speed follow

https://brainly.com/question/6504879

#SPJ2

5.6 Show your work
x 7.3
———

Answers

Hello there!

[tex]5.6*7.3[/tex]

Explanation:

↓↓↓↓↓↓↓↓

First you had to multiply without the decimal points, and then you put the decimal point it should be the correct answer.

[tex]56*73=4088[/tex]

5.6 it has one decimal place.

7.3 it has one decimal place.

Therefore, the answer should be the two decimal places.

[tex]=40.88[/tex]

Answer⇒⇒⇒⇒⇒40.88

Hope this helps!

Thank you for posting your question at here on Brainly.

Have a great day!

-Charlie

What are fact family's for 4,9,36

Answers

4 x 9 = 36

9 x 4 = 36

36/9 = 4

36/4 = 9

A surplus is

When you spend more than you have in income

When you spend less than you have in income

When you spend the same amount that you have in income

Another word for income

Answers

It is when you spend less money than you have in income because a surplus is when there is extra money left over.

A surplus is "When you spend less than you have in income".

What is income?

Income is the monetary value that a person earns against a service or a business.

When the person spends less than his income or spends less than the expected expenditure, then the extra saved money is known as a surplus.

Hence, A surplus is "When you spend less than you have in income".

Learn more about income here:

https://brainly.com/question/14732695

#SPJ2

Simplify: x+2/x^2-6x-16 ÷ 1/9x

Answers

Answer:

Step-by-step explanation:

Find the value of a if x=3 is a solution to the equation x/a=7

Answers

if x=3
3/a=7
a(3/a)=a(7)
3=7a or 7a=3
(7a)/7=3/7
a=3/7

John invests a sum of money in a retirement Account with fixed annual interest rate of 2.63% compounded continuously.After 15 years the balance reaches 1,912.41.What was the amount of initial investment

Answers

Answer: The amoun of the initial value was $1,289.


Step-by-step explanation:

1. To solve this problem you must apply the formula shown below:

[tex]A=Pe^{rt}[/tex]

Where:

- [tex]A[/tex] is the account balance ([tex]A=1,912.41[/tex]).

- [tex]P[/tex] is the principal.

- [tex]r[/tex] is the annual interest ([tex]r=0.0263[/tex]).

- [tex]t[/tex] is the time in years ([tex]t=15[/tex]).

- [tex]e[/tex]=2.7182

2. You must substitute the values into the formula and then you must solve for [tex]P[/tex], as following:

[tex]1,912.41=Pe^{(0.0263)(15)}\\1,912.41=1.48P\\P=\frac{1,912.41}{1.48}\\P=1,289[/tex]

Answer:

$ 1,289

Step-by-step explanation:

p= 1289

Find the perimeter of the triangle.

Answers

The base is from 2 to 7, which is 5 units long.

The height is from 1 to 8, which is 7 units tall.

Using the Pythagorean theorem we can calculate the hypotenuse:

Hypotenuse = √5^2 +7^2=

√25 +49=

√74=

8.6


Perimeter = 5 + 7 + 8.6 = 20.6


The answer is C.

A theater can seat 120 people. The number of rows is 7 less than the number of seats in each row. How many rows of seats are there?

Answers

Let x be the number of rows.

If the number of rows is 7 less than the number of seats in each row, then the number of seats in a row is x+7. The total number of seats is

x·(x+7).

You know that a theater can seat 120 people, then

x·(x+7)=120.

Solve it:

[tex]x^2+7x-120=0,\\\\D=7^2-4\cdot (-120)=49+480=529,\ \sqrt{D}=23,\\\\x_1=\dfrac{-7+23}{2}=8, \ x_2=\dfrac{-7-23}{2}=-15.[/tex]

The number of rows must be positive, then x=8.

Answer: there are 8 rows with 15 seats at each.

140 students are going in a field trip. They fill up a total of 4 buses equally. How many students are on each bus?

Answers

Your answer is 35

Hope this helps

The answer is 35 students in each bus. You just have to divide the number of students (140) and the number of buses (4). Then you'll get 35

P=a+b-4 you have to solve for a

Answers

P = a + b - 4

subtract b from both sides

P - b = a - 4

add 4 to both sides

P - b + 4 = a

Final answer:

To solve for 'a' in the equation P = a + b - 4, you should subtract 'b' from both sides and add 4 to both sides to get a = P - b + 4.

Explanation:

The question asks to solve for a in the equation P = a + b - 4. To do this, we need to isolate a on one side of the equation. Thus, we start by subtracting b from both sides and then adding 4 to both sides. The resulting equation will be a = P - b + 4. This procedure is quite different than solving quadratic equations like ax² + bx + c = 0, where we have to use the quadratic formula -b ± √b² - 4ac / 2a to find the solutions.

Learn more about Solving Linear Equations:

https://brainly.com/question/18322830

#SPJ11

Help me to answer now ineed this
Please...

Answers

ANSWER TO QUESTION 1

[tex]\frac{\frac{y^2-4}{x^2-9}} {\frac{y-2}{x+3}}[/tex]

Let us change middle bar to division sign.

[tex]\frac{y^2-4}{x^2-9}\div \frac{y-2}{x+3}[/tex]

We now multiply with the reciprocal of the second fraction

[tex]\frac{y^2-4}{x^2-9}\times \frac{x+3}{y-2}[/tex]

We factor the first fraction using difference of two squares.

[tex]\frac{(y-2)(y+2)}{(x-3)(x+3)}\times \frac{x+3}{y-2}[/tex]

We cancel common factors.

[tex]\frac{(y+2)}{(x-3)}\times \frac{1}{1}[/tex]

This simplifies to

[tex]\frac{(y+2)}{(x-3)}[/tex]

ANSWER TO QUESTION 2

[tex]\frac{1+\frac{1}{x}} {\frac{2}{x+3}-\frac{1}{x+2}}[/tex]

We change the middle bar to the division sign

[tex](1+\frac{1}{x}) \div (\frac{2}{x+3}-\frac{1}{x+2})[/tex]

We collect LCM to obtain

[tex](\frac{x+1}{x})\div \frac{2(x+2)-1(x+3)}{(x+3)(x+2)}[/tex]

We expand and simplify to obtain,

[tex](\frac{x+1}{x})\div \frac{2x+4-x-3}{(x+3)(x+2)}[/tex]

[tex](\frac{x+1}{x})\div \frac{x+1}{(x+3)(x+2)}[/tex]

We now multiply with the reciprocal,

[tex](\frac{(x+1)}{x})\times \frac{(x+2)(x+3)}{(x+1)}[/tex]

We cancel out common factors to  obtain;

[tex](\frac{1}{x})\times \frac{(x+2)(x+3)}{1}[/tex]

This simplifies to;

[tex]\frac{(x+2)(x+3)}{x}[/tex]

ANSWER TO QUESTION 3

[tex]\frac{\frac{a-b}{a+b}} {\frac{a+b}{a-b}}[/tex]

We rewrite the above expression to obtain;

[tex]\frac{a-b}{a+b}\div {\frac{a+b}{a-b}}[/tex]

We now multiply by the reciprocal,

[tex]\frac{a-b}{a+b}\times {\frac{a-b}{a+b}}[/tex]

We multiply out to get,

[tex]\frac{(a-b)^2}{(a+b)^2}[/tex]

ANSWER T0 QUESTION 4

To solve the equation,

[tex]\frac{m}{m+1} +\frac{5}{m-1} =1[/tex]

We multiply through by the LCM of [tex](m+1)(m-1)[/tex]

[tex](m+1)(m-1) \times \frac{m}{m+1} + (m+1)(m-1) \times \frac{5}{m-1} =(m+1)(m-1) \times 1[/tex]

This gives us,

[tex](m-1) \times m + (m+1) \times 5}=(m+1)(m-1)[/tex]

[tex]m^2-m+ 5m+5=m^2-1[/tex]

This simplifies to;

[tex]4m-5=-1[/tex]

[tex]4m=-1-5[/tex]

[tex]4m=-6[/tex]

[tex]\Rightarrow m=-\frac{6}{4}[/tex]

[tex]\Rightarrow m=-\frac{3}{2}[/tex]

ANSWER TO QUESTION 5

[tex]\frac{3}{5x}+ \frac{7}{2x}=1[/tex]

We multiply through with the LCM  of [tex]10x[/tex]

[tex]10x \times \frac{3}{5x}+10x \times \frac{7}{2x}=10x \times1[/tex]

We simplify to get,

[tex]2 \times 3+5 \times 7=10x[/tex]

[tex]6+35=10x[/tex]

[tex]41=10x[/tex]

[tex]x=\frac{41}{10}[/tex]

[tex]x=4\frac{1}{10}[/tex]

Method 1: Simplifying the expression as it is.

[tex]\frac{\frac{3}{4}+\frac{1}{5}}{\frac{5}{8}+\frac{3}{10}}[/tex]

We find the LCM of the fractions in the numerator and those in the denominator separately.

[tex]\frac{\frac{5\times 3+ 4\times 1}{20}}{\frac{(5\times 5+3\times 4)}{40}}[/tex]

We simplify further to get,

[tex]\frac{\frac{15+ 4}{20}}{\frac{25+12}{40}}[/tex]

[tex]\frac{\frac{19}{20}}{\frac{37}{40}}[/tex]

With this method numerator divides(cancels) numerator and denominator divides (cancels) denominator

[tex]\frac{\frac{19}{1}}{\frac{37}{2}}[/tex]

Also, a denominator in the denominator multiplies a numerator in the numerator of the original fraction while a numerator in the denominator multiplies a denominator in the numerator of the original fraction.

That is;

[tex]\frac{19\times 2}{1\times 37}[/tex]

This simplifies to

[tex]\frac{38}{37}[/tex]

Method 2: Changing the middle bar to a normal division sign.

[tex](\frac{3}{4}+\frac{1}{5})\div (\frac{5}{8}+\frac{3}{10})[/tex]

We find the LCM of the fractions in the numerator and those in the denominator separately.

[tex](\frac{5\times 3+ 4\times 1}{20})\div (\frac{(5\times 5+3\times 4)}{40})[/tex]

We simplify further to get,

[tex](\frac{15+ 4}{20})\div (\frac{(25+12)}{40})[/tex]

[tex]\frac{19}{20}\div \frac{(37)}{40}[/tex]

We now multiply by the reciprocal,

[tex]\frac{19}{20}\times \frac{40}{37}[/tex]

[tex]\frac{19}{1}\times \frac{2}{37}[/tex]

[tex]\frac{38}{37}[/tex]

number 3.simplify 24cd/c

Answers

The answer is 24d because you have to simplify d_c first then you have 24c x  d_c  and then c cancels itself out so the answer is 24d.



The sum of 4 times a number and 7 is equal to 5

Answers

let the missing number be x
4x+7=5
step 1: subtract 7 from both sides
4x=-2
step 2: divide by 4 on both sides
x=-0.5
Final answer:

The question presents a basic algebraic problem. We translate the words into a mathematical equation, 4x + 7 = 5. After some simple manipulations (subtracting 7 from both sides and dividing the result by 4), we find that the value of x is -0.5.

Explanation:

The question presents a typical example of a simple equation in Mathematics. The first step in solving this problem involves interpretation. The statement 'The sum of 4 times a number and 7 is equal to 5' can be translated into this equation: 4x + 7 = 5. To obtain the value of x, we need to isolate it on one side of the equation.

We can proceed by subtracting 7 from both sides
to achieve 4x = -2. Finally, we divide both sides of the equation by 4 to obtain x = -0.5. Thus, the number in question is -0.5.

Learn more about Algebra here:

https://brainly.com/question/32436021

#SPJ2

PLEASE HELP!! WILL MARK BRAINLIEST! NO ONE HAS BEEN ABLE TO HELP!

Answers

Answer:  A


Step-by-step explanation:

Let us first observe behavior in only quadrant 1 .

On x-axis one small box represent one year.

On y-axis one small box represent  one dollar.

If we see the 1 year on x-axis its corresponding value of dollar on y -axis is in mid of 4 dollars and 5 dollars.

Now if we see the 2nd year on x-axis its corresponding value of dollar on y-axis is at 6 dollars .

It concluded that after each year 0.5 dollars per pound increases.

We can see the same behavior throughout the straight line.


Mr.santino needs a total of 406 forks for his restaurant. He currently has 278 forks .15 if each set has 12 forks ,what is the minimum number of sets of forks he should buy?

Answers

he should buy 11 sets of forks, hope this helped! <3

The area of a certain state is 840,000 miles. what is this area in scientific notation

8.4 x 10^-4


84 x 10^-3


84 x 10^3


8.4 x 10^5


Plz help asap!!!!

Answers


[tex]84 \times10 \sqrt{?} [/tex]

The answer is D the last one.

If f(x)= 2x^2 -3x+1, find f(3)-f(2).

A. 0
B. 7
C. 17
and briefly explain pleaseee

Answers

f(3) = 2x² - 3x + 1

2(3)² - 3(3) + 1

18 - 9 + 1

F(3) = 10

f(2) = 2(2)² - 3(2) + 1

8 - 6 + 1

f(2) = 3

f(3) - f(2)

10 - 3

f(3) - f(2) = 7 because you find f(3) = 10, and f(2) = 3, and plug in the answer you found. This gives you 10 - 3, which is 7.

The value of f(3) - f(2) is 7 if the function f(x) = 2x² - 3x + 1 the correct answer is option B: 7.

To find f(3) and f(2), we need to plug the respective values of x into the given function f(x) = 2x² - 3x + 1 and then subtract the results.

f(3):

f(3) = 2(3)² - 3(3) + 1

f(3) = 2(9) - 9 + 1

f(3) = 18 - 9 + 1

f(3) = 10

f(2):

f(2) = 2(2)² - 3(2) + 1

f(2) = 2(4) - 6 + 1

f(2) = 8 - 6 + 1

f(2) = 3

Now, let's find f(3) - f(2):

f(3) - f(2) = 10 - 3 = 7

So, the value of f(3) - f(2) is 7.

The correct answer is option B: 7.

To know more about function click here :

https://brainly.com/question/34734445

#SPJ2

im confused, picture up above

Answers

Answer:

Its Option B

Step-by-step explanation:

Total Amount of Ice Cream = 2/3 cup

Ice Cream Taken = Two Scoops of 1/6 cups = 2 x 1/6 = 2/6

Ice Cream Left = Total Amount of Ice Cream - Ice Cream Taken

                         =  2/3  -  2/6

                         =   2/6

Hope That explains it!

Brainliest?

There is an animal farm where chickens and cows live. All together, there are 82 heads and 192 legs. How many chickens and cows are there on the farm?

Answers

Answer:

There are 14 cows and 68 Chicken in the farm.

Step-by-step explanation:

A Cow has 4 legs

Chicken has 2 legs.

Lets take there [tex]x[/tex] chickens AND,

there are [tex]y[/tex] number of Cows.

Now we can write two equations for the number of heads and legs.

For the number of heads we can write,

[tex]x+y=82[/tex] <--------- 1st equation

For the number of legs we can write,

[tex]2x+4y=192[/tex] <------ 2nd equation

We can now solve the simultaneous equations to find [tex]x[/tex] and [tex]y[/tex]

Multiply 1st equation by 2 and deduct it from 2nd equation to remove [tex]x[/tex]

⇒[tex]2x+4y-2*(x+y)=192-164[/tex]

⇒[tex]2x+4y-2x-2y)=112-164[/tex]

⇒[tex]2y=28[/tex]

⇒[tex]y=14[/tex]

Therefore, there are 14 cows in the farm.

Now we can substitute the [tex]y[/tex] value to the 1st equation and find [tex]x[/tex] value.

[tex]x+14=82[/tex]

[tex]x=68[/tex]

Therefore, there are 68 chickens in the farm.

Other Questions
A pharmacist is filling small empty bottles with cough syrup from a larger bottle. He can solve the inequality to find the number of small bottles, x, that can be filled from the larger bottle and still have 250 milliliters left in the larger bottle. Which statement describes the number of small bottles the pharmacist can fill? What is the estimated cost for 7.8 pounds of potatoes at 3.89 Rising temperatures in the Arctic Ocean can lead to large die-offs of phytoplankton, which are autotrophs. What would most likely happen in an Arctic ecosystem if the phytoplankton population decreased? Help ASAP please!!!First answer and correct answer gets the brain... Glenn has a family history of diabetes which life style change should he adopt to lower his chances of developing diabetes which two islands are part of the british isles Question: lucia is nurse at a hostpital. Over time she works 150 hours each month.How many hours does she work in a year?answer: 1800 hours Please simplify the following distributive property expression:4(3x-5)I got 12x-20, is that correct? Marine organisms adapted to the coldest temperatures and the highest salinity levels would inhabit which zone? 113 surveys 72 answerd yes 41 answerd no whats the percentage How does tripling the side lengths of a right triangle affects its area? Find the value of z such that 0.9544 of the area lies between z and z. Round your answer to two decimal places. What were the goals of the Allie in Europe what is the missing length of a square what is most likely the purpose of this passage Solve for x.10 Um what is 20 +10 I want to give points How was Portuguese trade in India different from that in the Americas?A.It offered great wealth from gold and silver.B.It involved exchanges with traders from China and Southwest Asia.C.It required the establishment of many colonial settlements.D.It did not involve violence against other cultures. What object is the type of matter that makes up the object and the way that matter is arranged Emre pays a $20 sign-up fee to join a video streaming service and $12 for each month of his membership. The equation c = 12w + 20 gives the total cost for w weeks. Which statement correctly describes what happens when w increases?